Stabilitas Pemerintahan Pasca Pemilihan Umum di Indonesia antara Checks and Balances dan Demokrasi Transaksional - Fuqoha Fuqoha; Arif Nugroho; Indrianti Azhar Firdausi (Ajudikasi : Jurnal Ilmu Hukum, 2019)
Realizing of implementation a democratic State, in Indonesian constitutional system is prepared by principles of constitutional democracy. The principle of constitutional democracy is carried out with the intention of implementing a democratic system with limited by constitution. Among the principles of democracy are the electoral system to elect State leaders and people's representatives. Good government will creation a government stability and political stability in realizing the goals and ideals of the State through the concept of checks and balances. The conception of checks and balances in a democratic frame can be realized with the principles of transformative democracy and / or transactional democracy. In the constitution of Indonesia, the principle of transactional democracy can occur before and after the general election of the President and Vice President. Transactional democracy can threaten government and / or political stability if group / coalition solidity is not created in carrying out checks and balances.